2021
DOI: 10.5195/jyd.2021.1001
|View full text |Cite
|
Sign up to set email alerts
|

Motivation (Constructs) Made Simpler: Adapting Self-Determination Theory for Community-Based Youth Development Programs

Abstract: Motivation is a key factor for enhancing psychological engagement among underserved youth. However, the abundance of motivational constructs complicates the translation of theory into practice by community-based youth development programs. This paper simplifies the translation process, presenting an actionable motivation model derived from Ryan and Deci’s (2000) self-determination theory (SDT) and its sub-construct, organismic integration theory (OIT). This model was developed by Youth Enrichment Services (YES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…An important aspect is that the satisfaction generated from interacting with other individuals could increase or decrease over time (Yildiz & Kiliç, 2021). In this way, it is confirmed that the attitude towards behaviour, subjective norms, and perceived behavioural control are influenced by the emotions resulting from interactions with others, especially regarding healthy eating behaviour (Baumeister & Leary, 1995;Jones et al, 2021).…”
Section: The Need For Relatedness As An Individual Needs From Self-de...mentioning
confidence: 78%
“…An important aspect is that the satisfaction generated from interacting with other individuals could increase or decrease over time (Yildiz & Kiliç, 2021). In this way, it is confirmed that the attitude towards behaviour, subjective norms, and perceived behavioural control are influenced by the emotions resulting from interactions with others, especially regarding healthy eating behaviour (Baumeister & Leary, 1995;Jones et al, 2021).…”
Section: The Need For Relatedness As An Individual Needs From Self-de...mentioning
confidence: 78%
“…According to Ertac & Tanova (2020), SDT is a far-reaching theory of motivation that includes several sub-theories. Self-determination theory provides a background for human motivation founded on the knowledge that when people's inherent psychological needs of relatedness, autonomy, and competence are developed to challenge themselves, their motivation to explore and master new skills can be enhanced (Jones et al, 2021) In opposition to other needs theories, in the SDT, competence, autonomy, and relatedness do not vary by the extent to which individuals possess them but by the degree to which the environment facilitates their satisfaction or frustration (Vansteenkiste et al, 2020). According to SDT, the three needs that can influence behavior is the environments that help the needs build autonomous and intrinsic types of motivation, consequently improving desired behaviors (Deci & Ryan, 2008).…”
Section: Theoretical Review 31 Self-determination Theorymentioning
confidence: 99%
“…SDT draws on controllable external motivators provided by the organization, individuals’ autonomous intrinsic motivators and amotivation to identify what drives behavior (Deci and Ryan, 2012). The SDT framework describes how individuals can become motivated when their innate needs are met and the objective at hand is both relevant and achievable (Jones et al , 2021). The taxonomy of motivation as presented by SDT identifies various regulatory styles, their associated processes and their perceived locus of causality (Deci and Ryan, 2000a).…”
Section: Literature Reviewmentioning
confidence: 99%